Seismic performance of beam bar anchorage in exterior reinforced concrete beam-column joint - Nancy Permatasari Widjaja (2009)
Being in proximity of subduction zones, Indonesia region is very vulnerable to earthquake disruption. Earthquake wave interruptions are recorded every minute proving how active the movement of earth tectonic plates around Indonesia is. Many cases of earthquake tremors have been countlessly noted in Indonesian history, including the recent ones: Bengkulu earthquake in 2007, Yogyakarta earthquake 2006, and the indisregarded massive Tsunami disaster in 2004. Lots of casualties, damaged infrastructures and million dollars have lost due to the catastrophe. There has to be preventive actions be taken to avoid future loss.